Identity and European Public Spheres in the Context of Social Media and Information Disorder - Kermer, Jan Erik (2020)
It was expected that the increasing coverage of EU affairs in national public spheres would lead to a greater sense of European belonging. The Internet was expected to foster this process. However, these expectations do not square with the current political climate of identity politics and the revitalisation of nationalism. How can this incongruence between theory and reality be understood? An intervening variable has added an unpredictability to the mix: information disorder. It is our view that this theory needs revising to include other intervening variables such as social media and information disorder. In this article, we argue that the current dynamic of Europeanised political communication is likely to compromise the civic and vertical components of EU-identity.